The sensitivity of gamma index analysis to detect multileaf collimator (MLC) positioning errors using Varian TrueBeam EPID and ArcCHECK for patient-specific prostate volumetric-modulated arc therapy (VMAT) quality assurance. Issue 1 (11th July 2017) - Maraghechi, Borna; Davis, Jack; Mitchell, Nicholas; Shah, Meeral; Fleck, Andre; Darko, Johnson; Osei, Ernest
Abstract: Background: Due to the increased degree of modulation and complexity of volumetric-modulated arc therapy (VMAT) plans, it is necessary to have a pre-treatment patient-specific quality assurance (QA) programme. The gamma index is commonly used to quantitatively compare two dose distributions. In this study we investigated the sensitivity of single- and multi-gamma criteria techniques to detect multileaf collimator (MLC) positioning errors using the Varian TrueBeam Electronic Portal Imaging Device TM (EPID) dosimetry and the ArcCHECK TM device. Materials and methods: All active MLC positions of seven intact prostate patients VMAT plans were randomly changed with a mean value of 0.25, 0.5, 1 and 2 mm and a standard deviation of 0.1 mm on 25, 50, 75 and 100% of the control points. The change in gamma passing rates of six gamma criteria of 3%/3 mm, 3%/2 mm, 3%/1 mm, 2%/2 mm, 2%/1 mm and 1%/1 mm were analysed individually (single-gamma criterion) and as a group (multi-gamma criteria) as a function of the simulated errors. We used the improved and global gamma calculation algorithms with a low dose threshold of 10% in the EPID and ArcCHECK software, respectively. The changes in the planning target volume dose distributions and the organs at risk due to the MLC positioning errors were also studied. Results: When 25, 50, 75 and 100% of the control points were modified by the introduction of the simulated errors, the smallest detectable errors with the EPID were 2, 1, 0.5 and 0.5 mm, respectively, using the multi-gamma criteria technique. Similarly for the single-gamma criteria technique errors as small as 2, 1, 1 and 1 mm applied to 25, 50, 75 and 100% of the control points, respectively, were detectable using a 2%/2 mm criterion. However, the smallest detectable errors with the ArcCHECK when using the multi-gamma criteria technique were 2, 2 and 1 mm when MLC errors were applied on 50, 75 and 100% of the control points. When only 25% of the control points were affected the ArcCHECK were unable to detect any of the errors applied. No noticeable difference was observed in the sensitivity using the single- or the multi-gamma criteria techniques with the ArcCHECK. Conclusion: The Varian TrueBeam EPID dosimetry shows a higher sensitivity in detecting MLC positioning errors compared with the ArcCHECK regardless of using the single- or the multi-gamma criteria techniques. Higher sensitivity was observed using the multi-gamma criteria technique compared with the single-criterion technique when using the EPID.